Approximated analytical frequency response of a pendulum structure attached with two orthogonal dynamic vibration absorbers - Viet, La Duc; Nghi, Nguyen Ba (Vietnam Journal of Mechanics, 2015)
Vibration of a pendulum can be reduced by single dynamic vibration absorbers (DVAs) moving in tangential or in normal direction of pendulum's orbit. The first DVA works in the linear zone while the second one works in the nonlinear zone. This paper uses the equivalent linearization technique to obtain an analytical form of the frequency response of a nonlinear pendulum structure, which is attached with both types of DVA. The numerical calculations are carried out to verify the analytical results. Some useful conclusions on the optimal parameters of the DVA can be found from the analytical solution.